KONTESTASI ORTODOKSI DAN FILSAFAT: STUDI PEMIKIRAN AL-GHAZALI DAN IBNU RUSYD - Farkhan Fuady; Abd Chair (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
The emergence of Islamic orthodoxy and philosophy created contestation between the two. The figure who directly confronted Muslim philosophers was Al-Ghazali. He criticized Muslim critics on several issues. Next, Ibnu Rushd appeared to answer Al-Ghazali criticism. Contestation between the two occurred in the 11th-12th century AD, but the discourse of both ideas is still widely studied today. This article analyzes the contestation of Islamic orthodoxy and philosophy in the 11th-12th centuries AD. The method used is qualitative with the type of library research. The research source comes from the works of Al-Ghazali and Ibn Rushd and was analyzed using descriptive analysis. This research shows that the contestation between orthodoxy and philosophy has been going on for a long time. As an orthodox person, Al-Ghazali tried to criticize philosophers through several issues related to philosophers' views, such as the eternity of nature, the knowledge of God, and physical resurrection, which Ibnu Rushd then answered as a philosopher. The contest between the two has experienced a long history of debate and debate. It is also necessary to understand these differences because both are an integral part of Islamic intellectual history. Both approaches have advantages and disadvantages, giving rise to dialogue and discussions relevant to the contemporary Islamic era. It should also be noted that both have a role in completing the understanding of Islam.